The impact of leverage on stock returns: an empirical test on the Australian stock market - Thuy Linh, Doan (2009)
Asset pricing model is no longer a new topic to theoretical finance but it still maintains researchers’ interest until now. The role of firm characteristics in explaining the stock returns becomes more and more significant in the empirical studies. The Fama French three factor is the most famous model of testing the firm characteristics: size effect and book to market effect on stock returns. However, this model does not include leverage, one of the most important firm characteristics. Starting from this idea, the study is conducted to examine the relationship between stock returns and leverage along with measuring the leverage’s contribution to the model’s explanatory power. Data consists of 50 companies in the S&P/ASX 200 index of Australian Stock Exchange over the period 2005-2009. It is found that there is a significantly negative relationship between leverage and stock returns. Nonetheless, the test of explanatory power reports that leverage does not contribute to the explanatory power of the model.